Aplicación de SIG y fuentes secundarias en la detección de conflictos de usos de suelo : Caso de estudio: cuenca del Gato, provincia de Buenos Aires - Andrade, María Isabel (2012)
In this presentation, we report the factors that affect territorial planning in the Del Gato Stream Basin, La Plata municipality, Buenos Aires province. The main objective is to obtain information about land uses that help us to analyze the distribution of population and economic activities in the area, and to detect land use incompatibilities. Our starting-point is the hypothesis that land uses are in strong conflict, and this situation exposes local population to a high sanitary risk. By the use of GIS, we spatially analyze secondary data, in order to create new data to be compared with previous information. Thus, we propose a useful procedure to study areas that present land-use conflicts. At present, we have identified the main land-use conflicts that exist in the high and middle basin. Dangerous industries are located in residential zones and in areas with flood risk. Related to territorial planning, we have compared “legal land uses” to “real land uses”, to find incompatibilities. We have analyzed the distribution of population in the study area, and it was possible to determine that zones with a higher number of precarious houses are located in the urban periphery next to the stream. The current administrative strategies have not resolved effectively these complex issues that affect a wide range of social actors.